Awareness of Toxic and Harmful School Plants and their Prevention and Protection for Learners Against Plant-Causing Emergencies - Cubillas, Ariel U; Cubillas, Trixie E (International Journal of Membrane Science and Technology, 2023)
The school greening program supports the inculcation among learners with the love of nature since it cultivates among them the significance of plants in making the learning space beautiful and healthy. However, people cannot just bring any beautiful ornamental plants as they please especially to a school campus. Plants ideally possess defense mechanisms to protect themselves from harm. Hence, they develop thorns, spikes, and scents to ward off any potential predators. A piece of knowledge about this plant defense mechanism as well as plants’ toxicity should be instilled among the adults in the learning space, particularly the teachers. Thus, this paper intends to ascertain the level of awareness of public school teachers on toxic and harmful plants commonly found in the classroom or school premises and determine the level of prevention and protection for learners against plant-causing emergencies. Results reveal that the teachers’ awareness particularly on making the learning space safe may have something to do with first aid application in case of emergencies and protecting children. The more the teachers aim to provide a wholesome and safe space for the learners, the more they try to learn and apply first aid as their way of protecting their learners. It is recommended that the school should provide first aid kits with antihistamines and teachers should be provided by the concerned agencies list of plants that may potentially be toxic or harmful to the schoolchildren. Furthermore, school gardening activities must be done with great precautions.